Multi-omics integration reveals chromatin-associated lncRNA prognostic model in lung adenocarcinoma: Bridging GWAS, transcriptome and clinical outcomes - Xiao Zhu; Zhuolong Xiong (Medicine in Omics)
Background: Lung adenocarcinoma (LUAD) is characterized by low overall survival rates. This research aims to explore the association between long non-coding RNAs (lncRNAs) and chromatin histone methylation/demethylation modifiers in LUAD. Methods: Datasets from The Cancer Genome Atlas (TCGA), Molecular Signatures Database (MSigDB), and IEU Open genome-wide association studies (GWAS) database were analyzed. A prognostic risk model for LUAD was developed based on 32 lncRNAs linked to histone modification. The relationship between lncRNAs and the high-risk group of lung cancer was evaluated, and GO/KEGG analysis was conducted to investigate the connection between chromatin histone modification-related lncRNAs and biological processes/pathways. Mendelian Randomization methods, including Inverse Variance Weighted (IVW) and Bayesian Weighted Mendelian Randomization (BWMR), were employed to validate the GO/KEGG results. MR-Egger intercept test, Cochran’s Q test, and leave-one-out Analysis were utilized to assess the sensitivity of Mendelian Randomization analysis. Tumor mutation burden (TMB) analysis was performed to evaluate the prognostic impact of high-risk patients with high TMB. Results: Identified lncRNAs, including AC025741.1 and NHS-AS1, demonstrated strong associations with the high-risk group. GO/KEGG analysis revealed significant correlations between chromatin histone modification-related lncRNAs and microtubule-based movement and cytochrome enzyme P450. Response to the renin-angiotensin agents is a protective factor for lung cancer, while response to glucocorticoids is a risk factor for lung cancer. Immunomarkers MDSC, CAF, and Exclusion showed positive correlations with the risk score, and the combined effects of CAF and MDSC were found to play a pivotal role in LUAD development and progression. Conclusion: Our study not only establishes a promising LUAD prognostic risk model with potential implications for immunotherapy but also identifies lncRNAs as immune markers for LUAD immunotherapy. Additionally, we validate the causal relationship between chromatin histone methylation-related pathways and lung cancer, bolstering our understanding from a genetic perspective and opening avenues for targeted interventions in LUAD treatment.